Transcerebellar Diameter: An Useful Tool to Estimate Gestational Age - Tandur , Roopa Kedarnath; Saima , Aiman; Chaudhary , Manish (Asian Journal of Medical Radiological Research, 2021)
Background: Gestational age is the most important factor for obstetrician to give appropriate management of pregnant women and to evaluate fetal development. An error in estimation of the gestational age (GA) results in adverse perinatal outcome. Many ultrasound parameters are used routinely for assessment of gestational age. Use of these parameters may be limited in some cases such as fetuses with abnormalities of skull vault and growth restricted fetuses. In such cases, the trancerebellar diameter (TCD), may be used as it is least affected. This study was conducted with an objective to show that TCD is a useful tool for determining the gestational age in comparison to other already existing parameters. Subjects and Methods: This was a prospective study including 100 pregnant women between 15 to 40 weeks of gestation. Gestational age using TCD and other parameters was calculated and compared with gestational age based on last menstrual period (LMP). Results: Mean age of study group was 27.5 years. Correlation between gestational age and various ultrasound parameters showed that TCD correlated best with GA with a correlation coefficient of 0.989 and significant P value of <0.005. Mean TCD showed a linear relationship with gestational age in weeks. Conclusion: TCD serves a reliable parameter in estimation of GA in second and third trimesters since it shows good correlation with GA.